2023
DOI: 10.1111/ijcs.12942
|View full text |Cite
|
Sign up to set email alerts
|

Public service announcements: A literature review and way forward

Abstract: This paper presents a literature review of public service announcements (PSAs). Using the SPAR‐4‐SLR protocol, we uncover 119 articles on PSAs in the domains of corporate social responsibility (CSR), the environment, health, finance, safety, and security. The literature review reveals that PSA makers may elicit empathy during their appeal and also juxtapose PSAs with narratives. Further, they may consider using fear, humour, and nurturance appeals. We cull the key takeaways from each domain and identify common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 174 publications
(300 reference statements)
0
1
0
Order By: Relevance
“…Due to the increased adoption of social messages in the commercial and non‐commercial streams along with the imbibed nature of social messages (Brochado et al, 2017; Sivakumaran et al, 2023), we have examined the factors identified in the context of social marketing communication for this study. We have also considered the increasing expenditure on socially conscious advertising, which aims to appeal to conscious consumers who look for products that reflect their sensitivities to social causes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increased adoption of social messages in the commercial and non‐commercial streams along with the imbibed nature of social messages (Brochado et al, 2017; Sivakumaran et al, 2023), we have examined the factors identified in the context of social marketing communication for this study. We have also considered the increasing expenditure on socially conscious advertising, which aims to appeal to conscious consumers who look for products that reflect their sensitivities to social causes.…”
Section: Introductionmentioning
confidence: 99%